The role of women in the production of flowers during the Assyrian period - Aziz, Asst.L.Zhala Abubakr; Mohammed, L.Khana Akram (Sulaimani Journal for Humanities, 2026)
Mesopotamian women have always been pioneers in building the civilization of the region. They have always played a significant role in all aspects, especially those women who lived in temples and palaces (Scent + Flower) was the use of chemical methods, especially cosmetic and health treatment products, so the name of the tablet raises two important aspects; The first is the role of women as scientists and craftsmen. The second is the creation of perfumes and flowers as a necessary beauty subject in ancient and modern times. The importance of perfumes has continued throughout the ages. As for Mesopotamia, the information we have from cuneiform texts and archaeological remains confirms this industry as strong evidence that its inhabitants found beauty in health and fragrance. This study also includes a summary in Kurdish, Arabic and English, the most important results and a list of sources. In the first part, the role of Mesopotamian women in the production of perfumes is explained and with the introduction of the alchemical lady and Gulaw Taputi, in the second part, the paper discusses the use of aromatic substances. The third and final part explains the most important methods of producing perfume and how to extract it from natural materials such as wood and flowers, and the most important picture of this chemical process for the production of perfume.
Keywords: Taputi; tablet; Middle Assyrian period; palace; round